Prognosis of Traumatic Injuries to the Anterior Teeth (Treated in Shahid Beheshti and Tehran Dental Schools During 1996-2001) - Asnaashari, Mohammad; Amin Tavakkoli, Mohammad; Shafiei Ardestani, Sara (Iranian Endodontic Journal, 2010)
INTRODUCTION: Traumatic injuries to the teeth are among the most serious dental accidents, with the anterior teeth being mostly affected. Some consequences of dental trauma include misshaping, speech defects, psychological and social effects. The knowledge of the field can reduce the suffering, cost, and the time for patients, parents, and health care providers. The aim of this study was to investigate the treatment prognosis of anterior traumatized teeth in patients referred to Endodontics and pediatrics Departments of Shahid Behesthi and Tehran Dental Schools during 1996-2001. MATERIALS AND METHODS: Fifty patients participated in this descriptive study. All affected by trauma to the teeth and completing the proposed treatment. Retrospective data, based on trauma forms as well as the clinical notes a questionnaire prepared for the study and analyzed in terms of age, gender, the type of trauma and etiology. RESULTS: Eighty four percent of the studied traumatized teeth were maxillary centrals. Falling-outs are most frequent cause of the traumas (56.5%), followed by sport and play events (30.4%). Enamel- dentin fractures with and without pulpal involvement were the most prevalent trauma types. Most of the selected treatment procedures were involved with pulp and periapical areas. CONCLUSION: Based on the finding of the study, the prognosis of traumatized anterior teeth in patients referred to the studied centers was estimated to be good.